Implantable Organic Artificial Synapses Exhibiting Crossover between Depressive and Facilitative Plasticity Response. (20th October 2021) - Calandra Sebastianella, Gioacchino; Di Lauro, Michele; Murgia, Mauro; Bianchi, Michele; Carli, Stefano; Zoli, Michele; Fadiga, Luciano; Biscarini, Fabio
Abstract: Organic neuromorphic devices mimic signal processing features of biological synapses, with short‐term plasticity, STP, modulated by the frequency of the input voltage pulses. Here, an artificial synapse, made of intracortical microelectrodes, is demonstrated that exhibits either depressive or facilitative STP. The crossover between the two STP regimes is controlled by the frequency of the input voltage. STP features are described with an equivalent circuit where an inductance component is introduced in parallel with the RC circuit associated with poly(3, 4‐ethylenedioxythiophene)/polystyrene sulfonate (PEDOT/PSS)||electrolyte interface. The proposed RLC circuit explains the physical origin of the observed STP and its two timescales in terms of charge build up in PEDOT/PSS. Abstract : Depressive and facilitative short‐term plasticity coexist in implantable organic artificial synapses and can be elicited at will by simply varying the input frequency. A unified equivalent circuit model of such devices explains the phenomenon, unveiling a pseudo‐inductive contribution to model poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate transient response in neuromorphic devices.